INNOVATIVE APPROACHES TO THE USE OF MEDICINAL PLANTS IN MODERN PHARMACY - НІКІТІНА, ОЛЬГА; РОБАК, АННА; ЦИБА, ДАНІЇЛ (Technologies and Engineering, 2024)
The purpose is to study approaches to the involvement of plants in the technology of production of pharmaceutical preparations. To conduct an analysis of ways of innovative use of plants in modern chemical-pharmaceutical and biopharmaceutical technologies. Methodology. General scientific and special methods of analysis and synthesis were used to study scientific and scientific-practical works of domestic and foreign scientists on studying ways of innovative use of plants in modern pharmaceuticals and abstract-logical ones when drawing conclusions. Results. Modern approaches to the discovery of herbal medicines are analyzed, relating to the search for promising botanical objects, the methodology for the extraction and separation of natural compounds, new concepts for establishing pharmacological action based on plant pharmacophylogeny, polypharmacology and network pharmacology. Examples of modern natural compounds are given - leaders of plant origin, which are used in evidence-based medicine and are the basis for the creation of new medicines, as well as Internet database resources for establishing the target pharmacology of plant compounds. The use of molecular plant farming as an alternative in the biotechnology of recombinant biomolecules is indicated. Scientific novelty. A transdisciplinary approach to using the potential of medicinal plants in the development of innovative drugs involving ethnopharmacology, plant chemosystematics, phytochemistry, pharmacology and bioinformatics is substantiated. Practical significance. Establishing innovative areas for the use of medicinal plants will increase the success of the discovery of drugs for the treatment of common and orphan diseases, reduce the cost of developing herbal drugs, and reduce the travel time of biologically active compounds from research to production and use in practical medicine.